Assessment of validity of the national public health performance standards: the local public health performance assessment instrument - Beaulieu, Joyce; Scutchfield, F Douglas (Public health reports (1974), 2002)
The National Public Health Performance Standards Program (NPHPSP) has developed performance standards measurement instruments, based on the 10 "Essential Services of Public Health" that are being tested in several states. This article is a report on the face and content validity of the instrument designed for local public health systems. Judgments about the face validity of the standards were obtained in a survey of local public health systems that had used the instrument in a test state. The validity of each standard was addressed along the following dimensions: the importance of the standard as a measure of the Essential Service; its completeness as a measure; and its reasonableness for achievement. All standards for each Essential Service were then judged in terms of their completeness in measuring performance of that service. Respondents judged the standards to be highly valid measures of local public health system performance. Some respondents had reservations about whether standards related to "enforcing laws and regulations" were achievable. Holding local public health systems accountable for the activities of other agencies was a factor mentioned in conjunction with those standards. The NPHPSP standards have face and content validity for measuring local public health system performance. Further testing of their validity and reliability is continuing.